Placing Jules Itier’s Body of Work in Perspective - Massot, Gilles (International Journal on Stereo & Immersive Media, 2019)
The photographic work done by Jules Itier around the China Sea in 1844-45 while travelling with the Lagrené Mission was thought to be, up until recently, some of the earliest photographs of several Asian countries. A new round of research has established that they are indeed the earliest extant photographs of Asia, while proposing new readings of a few outstanding daguerreotypes such as the DaNang fort and the 360º panorama of Canton made-up of 14 plates. This paper looks at the longer term and theoretical implications of what we can now call a ground-breaking body of work.